2006
DOI: 10.1111/j.1750-3841.2006.00108.x
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Escherichia coli O157:H7 During Production of Snack Sticks Made from Beef or a Venison/Beef Fat Blend and Directly Acidified with Citric or Lactic Acid

Abstract: The effectiveness of a typical production process for eliminating Escherichia coli O157:H7 in directly acidified snack sticks made with beef or a venison/beef fat blend was evaluated for formulations of different fat content (10% and 25%) and type of direct acidulant (encapsulated citric or lactic acid). Raw batter inoculated with E. coli O157:H7 to an initial level of approximately 7.1 log CFU/g was stuffed into 21‐mm casings and processed according to a thermal‐processing schedule typical of those used comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
(25 reference statements)
3
7
0
Order By: Relevance
“…In our study, fat level (type of beef) had no effect ( P ≥ 0.05) on microbial (total and E. coli O157:H7) counts, with few exceptions where this effect was negligible and had no practical significance (Table 7 and 8). Overall, our findings agree with those of Stoltenberg and others (2006) who reported that fat content (10% or 25%) did not affect E. coli O157:H7 counts during the production of beef snack sticks.…”
Section: Resultssupporting
confidence: 92%
“…In our study, fat level (type of beef) had no effect ( P ≥ 0.05) on microbial (total and E. coli O157:H7) counts, with few exceptions where this effect was negligible and had no practical significance (Table 7 and 8). Overall, our findings agree with those of Stoltenberg and others (2006) who reported that fat content (10% or 25%) did not affect E. coli O157:H7 counts during the production of beef snack sticks.…”
Section: Resultssupporting
confidence: 92%
“…(2007) study, no differences in log reductions were determined between fat contents for all‐beef or venison with beef fat summer sausages. This similar trend also was observed by Stoltenberg et al . (2006) for a thermal process used to control E. coli O157:H7 populations in snack sticks with 10 and 25% fat levels.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, our study demonstrates the ability to achieve lethality with a high RH during the thermal process. To achieve a lower MPR, a drying step could be implemented similar to one described by Stoltenberg et al . (2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15% fat) subjected to a circulating water bath (75°C). Kotrola and Conner (1997) and Stoltenberg et al (2006) also reported that fat content had no significant effect on the inactivation of E. coli O157:H7 when processed by thermal treatment. Inactivation of E. coli O157:H7, salmonellae, Campylobacter jejuni, Listeria monocytogenes and Staphylococcus spp.…”
Section: Introductionmentioning
confidence: 98%